Political micro-targeting: a Manchurian candidate or just a dark horse? - Balázs Bodó; Natali Helberger; Claes H. de Vreese (Internet Policy Review, 2017)
Political micro-targeting (PMT) has become a popular topic both in academia and in the public discussions after the surprise results of the 2016 US presidential election, the UK vote on leaving the European Union, and a number of general elections in Europe in 2017. Yet, we still know little about whether PMT is a tool with such destructive potential that it requires close societal control, or if it's "just" a new phenomenon with currently unknown capacities, but which can ultimately be incorporated into our political processes. In this article we identify the points where we think we need to further develop our analytical capacities around PMT. We argue that we need to decouple research from the US context, and through more non-US and comparative research we need to develop a better understanding of the macro, meso, and micro level factors that affect the adoption and success of PMTs across different countries. One of the most under-researched macro-level factors is law. We argue that PMT research must develop a better understanding of law, especially in Europe, where the regulatory frameworks around platforms, personal data, political and commercial speech do shape the use and effectiveness of PMT. We point out that the incorporation of such new factors calls for the sophistication of research designs, which currently rely too much on qualitative methods, and use too little of the data that exists on PMT. And finally, we call for distancing PMT research from the hype surrounding the new PMT capabilities, and the moral panics that quickly develop around its uses.
Keywords: 300; Political micro-targeting; Democracy